Diagnostic Efficacy of Aspergillus Galactomannan Lateral Flow Assay in Patients with Hematological Malignancies: A Prospective Multicenter Study. - ODABAŞI, ZEKAVER (My University, 2023)
Background A rapid and reliable diagnostic test is needed to reduce mortality through early diagnosis of invasive aspergillosis (IA) in patients with hematological malignancies. Objective To evaluate the efficacy of serum and bronchoalveolar lavage (BAL) Aspergillus galactomannan lateral flow assay (GM-LFA) in IA diagnosis and determine the correlation of GM-LFA with GM enzyme immunoassay (GM-EIA) in patients with hematological malignancies. Methods In this prospective multicenter study, we used serum and BAL fluid samples from patients with hematological malignancies and suspected IA and performed GM-LFA and GM-EIA. According to the EORTC/MSGERC criteria, patients were grouped as proven (n = 6), probable (n = 22), possible IA (n = 55), or no IA (n = 88). The performance of serum GM-LFA at 0.5 optical density index (ODI) and area under the curve (AUC) were calculated. Spearman’s correlation analysis and kappa statistics were performed to determine the agreement between the tests. Results GM-LFA showed an AUC of 0.832 in proven/probable IA (sensitivity [SEN], specificity [SPE], negative predictive value [NPV], and diagnostic accuracy were 75%, 100%, 92.6%, and 93.9%, respectively, at a 0.5 ODI) versus that in no IA. A moderate positive correlation was noted between the GM-LFA and GM-EIA scores (p = 0.01). The observed agreement between the tests at 0.5 ODI was almost perfect (p \0.001). After excluding patients who received mold-active antifungal prophylaxis or treatment, the SEN, SPE, NPV, and diagnostic accuracy for proven/probable IA were 76.2%, 100%, 93.3%, and 94.5%, respectively. Conclusions Serum GM-LFA demonstrated high discriminatory power and good diagnostic performance for IA in patients with hematological malignancies.
Keywords: Enzyme immunoassay; Galactomannan; Hematological malignancy; Invasive aspergillosis; Lateral flow assay